LCNEC of Nasal Cavity: Diagnostic and Treatment Modalities—Case Report and a Narrative Review - Jalal, Gaurav; Tilak, T.V.S.V.G.K. (Indian Journal of Medical and Paediatric Oncology, 2025)
Large cell neuroendocrine carcinoma (LCNEC) of the nasal cavity is a rare epithelial malignancy with only a few cases reported to date. In this article, we present a case report of a 48-year-old male, who presented with a history of epistaxis and nasal blockage for over 1 year and was initially diagnosed as undifferentiated carcinoma further confirmed as LCNEC by histological findings and immunohistochemistry. The patient was managed by neoadjuvant chemotherapy followed by concurrent chemoradiotherapy. After follow-up for 18 months, the patient continues to be in complete clinical, histopathological, and radiological remission. The following report also discusses the rarity, presentation, and various treatment modalities and their outcomes as per current knowledge. Essentially, through this article, we want to highlight the crucial role of the degree of differentiation in such malignancies, the outcome of different treatment modalities used till now, and how these aspects play a crucial role in the treatment and prognosis of such carcinomas.
Keywords: concurrent chemoradiotherapy; large cell neuroendocrine carcinoma; nasal cavity